Automated systems only: why CISOs should switch off their dumb machines. Issue 9 (September 2019) - Young, Spencer
Abstract : Cyber security is supposed to reduce risk and be cost effective at the same time. It's supposed to take the burden of legwork away from the CISO and his or her team. It's supposed to reduce the financial and reputational risk posed by malicious actors in an efficient, intelligent manner. Cyber security is supposed to reduce risk. What it's not supposed to do is generate reams of near-to-useless information, burying the security team in an avalanche of flags and alerts. Automating processes ensures that common threats are caught and dealt with early. Security orchestration, automation and response (SOAR) can help, stitching together an organisation's disparate policy enforcement infrastructure, such as firewalls, gateways and other types of controllers, as well as existing event management systems, explains Spencer Young of Imperva.